Novel Poly Deep Eutectic Solvents Based Supported Liquid Membranes for CO2 Capture - Ishaq, Manzar; Gilani, Mazhar Amjad; Afzal, Zobila Muhammad; Bilad, Muhammad Roil; Nizami, Abdul-Sattar; Rehan, Mohammad; Tahir, Eza; Khan, Asim Laeeq (Frontiers in Energy Research, 2020)
The poly deep eutectic solvents (PDESs), a potential substituent to ionic liquids, have emerged as relatively new material and have been successfully applied in catalysis, nanotechnology, and, more importantly, in gas separation. Herein, the PDESs were incorporated for the first time in the CO2 capturing membranes to exploit their inherent advantages in acid gas capture. The PDESs were synthesized by mixing choline chloride (hydrogen bond acceptor-HBA) and two hydrogen bond donors-HBDs (polyacrylic acid & polyacrylamide) separately in different molar ratios. The physical changes of the resulting homogeneous mixture along with the FTIR confirmed the successful synthesis of the PDESs. Afterward, these PDESs were impregnated into microporous polyvinylidene fluoride (PVDF) membrane support to fabricate supported liquid membranes (SLMs). The gas performance of the prepared PDES-SLMs was tested under pure and mixed-gas conditions for CO2, CH4, and N2. The factors affecting the practical application of SLMs, such as the effect of composition of the PDESs, temperature, and volume fraction of the CO2 in the feed gas, were investigated systematically. The prepared PDES-SLMs showed significant CO2 permeabilities up to 27 Barrer as well as remarkably high CO2/CH4 and CO2/N2 selectivities of the order of 55.5 and 60, respectively. It was observed that by increasing the choline content and the temperature, the activation energy required for CO2 capture decreased, which enhanced the membrane performance (permeability and selectivity). This can be ascribed to the basicity, molar free volume, and the H-bonding strength of the synthesized PDESs. The green potential, low cost, and the significant gas separation performance make theses PDESs a favorable alternative to the competing PILs in capturing the greenhouse acid gases.